Research trend of Arabic language teaching in the world: Systematic literature review based on Scopus database - Z. Zikriah; Lailatul Mauludiyah (Universitas Muhammadiyah Malang, 2024)
Arabic is a very important communication language in the world, especially among Muslims. There has been a lot of research related to Arabic language teaching, so it is necessary to analyze these trends. This systematic literature review aims to analyze trends in Arabic language teaching in the world (2008-2023), so that it can become a reference for research and development of current and future Arabic language teaching themes. Article searches were carried out in the Scopus database. Data is saved in *CSV and *RIS formats, synchronized with Mendeley and visualized with VOS-viewer. We used the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) model to determine truly appropriate articles (inclusion), resulting in 21 appropriate articles. The trend of publications related to the Arabic language teaching theme shows that interesting. We discuss year trends, research methods used, dominant authors, most cited authors, and the relationship between keywords (there are four main keywords). Discussions were also held regarding the dominant author's country of origin, collaboration, and the number of authors per article. We formulated five Arabic Language Teacher Profiles based on a study of the 21 articles. It is recommended that Arabic language teaching research and publications need to be promoted so that it becomes global attention and international collaboration occurs. We also suggest that future researchers can focus more on the assessment and evaluation aspects.